Auffindbarkeit, Wahrnehmbarkeit, Akzeptabilität Webseiten von Behörden in Leichter Sprache vor dem Hintergrund der rechtlichen Lage - Lang, Katrin (Frank & Timme, 2021)
Many public authorities are now obliged to use plain language on their websites. The aim is to improve the participation of people with disabilities. But are the legal requirements and the resulting textual practice suitable for achieving this goal from the perspective of accessible communication? To answer this question, Katrin Lang looks at the categories of "findability", "perceptibility" and "acceptability", which have been little addressed in research so far. She shows why many texts created on the basis of the Disability Equality Act and the Barrier-Free Information Technology Ordinance (BITV) have deficiencies in the area of acceptability and contain a so-called "motivation barrier". In addition, Lang explains how it is possible to make official websites at federal, state and municipal level not only findable, perceptible and understandable for people with communication impairments, but also acceptable and actionable.